The Range of Motion (ROM) in Increasing Muscle Strength in Stroke Patients : Literature Review - Septianingrum, Yurike; Subairi, Moh (Journal of Applied Nursing and Health, 2024)
Background: Proper care is essential for the prevention of mental and physical impairment in patients with Sroke illness. There is a golden time of less than six hours during which people can recuperate fully after a stroke. Disability and physical weakening, including a loss of muscle strength, may occur if treatment is not maximized within that time frame. The purpose of the literature review is to determine the importance of Range of Motion (ROM) in Increasing Muscle Strength in Stroke Patients. Methods: Use PRISMA Approach. The research stage is to make selections by paying attention to the quality of the journal. Furthermore, articles from journals that are considered less relevant are excluded. Literature obtained from 7 articles relevant to Google Scholar, Indonesia One Search, DOAJ, and Garuda with the keywords Range of Motion, Muscle Strength, Stroke. Results: After a review of selected articles, the results given Range of Motion have a good impact on increasing muscle strength in stroke patients. Conclusion: The Range of Motion (ROM) can be applied in health program for in Increasing Muscle Strength in Stroke Patients